2013
DOI: 10.5455/2319-2003.ijbcp20131003
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary pharmacological investigation of the ischuretic property and safety of a hydro-ethanolic extract of Amaranthus spinosis (Fam: Amaranthaceae)

Abstract: Background: Ischuria is a health and social problem, having a negative impact on sufferers. This study therefore was a preliminary investigation of the ischuretic property and safety for use of a hydro-ethanolic extract of Amaranthus spinosus used traditionally in managing ischuria. Methods: Phytochemical screening, thin layer chromatography and high performance liquid chromatography were performed on the extract to establish fingerprints for identification. Acetylcholine, Nicotine, and the extract were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The aqueous-methanolic crude extract of A. spinosus was studied in vivo in mice and in vitro using isolated tissue preparations and Amaranth (A. cruentus) Seeds Isolated peptide NIH-3T3 cell line Anti-cancer [52] was validated to possess laxative, spasmolytic and bronchodilator properties [89] (Table 2). According to Koffuor et al [90], hydroethanolic extract of A. spinosus had contractile effect on rat urinary bladder (similar to acetylcholine and nicotine) and rabbit jejunum, possibly mediated via nicotinic, histaminic and muscarinic receptor stimulation. The extract was not lethal and a 240 mg/kg dose had no adverse effect on blood, liver and kidney metabolic function; thus being safe for use in ischuria.…”
Section: Other Propertiesmentioning
confidence: 99%
“…The aqueous-methanolic crude extract of A. spinosus was studied in vivo in mice and in vitro using isolated tissue preparations and Amaranth (A. cruentus) Seeds Isolated peptide NIH-3T3 cell line Anti-cancer [52] was validated to possess laxative, spasmolytic and bronchodilator properties [89] (Table 2). According to Koffuor et al [90], hydroethanolic extract of A. spinosus had contractile effect on rat urinary bladder (similar to acetylcholine and nicotine) and rabbit jejunum, possibly mediated via nicotinic, histaminic and muscarinic receptor stimulation. The extract was not lethal and a 240 mg/kg dose had no adverse effect on blood, liver and kidney metabolic function; thus being safe for use in ischuria.…”
Section: Other Propertiesmentioning
confidence: 99%
“…Email: zipak1@yahoo.com Author(s) agree that this article remain permanently open access under the terms of the Creative Commons Attribution License 4.0 International License Source: Study amaranth is regarded significantly higher than several protein foods such as milk and soya bean and is therefore used as an important dietary supplement for HIV/AIDS patients in some African countries (Alemayehu et al, 2015). In addition, Amaranthus species has medicinal properties against constipation, fevers, hemorrhage, anaemia, kidney aliments and worms (Mensah et al, 2008;Koffuor et al, 2013) In Ghana, the crop is called "Aleefu" and commonly found in the Savannah, Deciduous and Forest agro-ecological zones (Dari et al, 2015). The crop plays significant role in the food security and income generation for farmers in both urban and rural settings.…”
Section: Introductionmentioning
confidence: 99%
“…Peptic ulcer is a disease characterized by mucosal damage that usually occurs in the stomach and proximal duodenum (Koffuor et al, 2013). It is a serious infection that occurs as a result of eating spicy food, stress, alcohol, stomach surgery, and Helicobacter pylor i (Bae et al, 2011).…”
Section: Introductionmentioning
confidence: 99%